Prenatal tobacco exposure is related to neurobehavioral modifications in infants of adolescent mothers (Clinics, 2011)
INTRODUCTION: Prenatal tobacco exposure interferes with neonatal outcomes. OBJECTIVE: To determine the neonatal neurobehavioral effects of in utero tobacco exposure. METHODS: This prospective cross-sectional study included healthy, term, with birth weight appropriate for gestacional age neonates without exposure to alcohol, drugs, or infections, born to adolescent mothers without psychiatric disorders or post-traumatic stress. Infants were classified according to in utero tobacco exposure, as identified by the Composite International Diagnostic Interview administered to mothers. Neurobehavior was assessed by the Neonatal Intensive Care Unit Network Neurobehavioral Scale. Both tools were administered between 24 and 72 hours after birth. Neurobehavioral outcomes were compared between exposed and nonexposed infants by ANOVA. The associations between neurobehavioral scores and number of cigarettes smoked were studied by linear correlation. RESULTS: During the study, 928 newborns of adolescent mothers were born, and 388 were included in the study. Of these, 23 were exposed to tobacco, and 365 neonates were not exposed. There were no differences between the groups in gestational age, birth weight, post-natal age at the exam, or time between last feeding and exam. Exposed neonates showed higher scores on arousal (p = 0.004), excitability (p = 0.003), and stress/abstinence signals (p = 0.019) and a lower score on regulation (p = 0.025). After adjusting for the type of anesthesia, mode of delivery, gender, age at neurologic exam, exam duration and time between last feeding and exam, differences in arousal and excitability remained significant. The mean number of cigarettes consumed daily was positively correlated with lethargy (p = 0.013) and inversely with attention (p = 0.043). CONCLUSIONS: Neonates exposed in utero to tobacco showed worse neurobehavioral performance between 24 and 48 hours of life.